Fake News in the Corporate World: A Rising Threat - Adriani, Roberto (European Journal of Social Science Education and Research, 2024)
Public opinion is used to thinking about fake news as a political phenomenon, a tool used to create dirty propaganda. It is true but it may be only the beginning. The literature is starting to realize that fake news may move from the political arena to the corporate world. If this should happen, fake news would overflow everywhere, making the post-factual society even more real. Fake news may become a dirty tool, used by dishonest companies to strike at their competitors’ reputation. The idea is that, till now, fake news has been used primarily for dirty propaganda and, marginally, to make money through the clickbait. However, since clickbait is a very basic approach, what we can expect is a breakthrough of fake news. From clickbait to much more sophisticated technologies and strategies to beat competitors dishonestly or to influence the global financial markets, for instance. A very dark big idea, in this case. It means that, in a post-factual society, even competition in the corporate world can be affected by fake news, fuelled by the abuse of new powerful technologies (Murgia M. and Kuchler H. 2017). The consequence is usually a decrease in sales and revenues, with a snowball effect. (Gupta S. 2016). Corporate reputation is an intangible as well as valuable asset. What makes it so valuable is that a good reputation can help the company to operate; on the other hand, a sullied reputation makes the company weaker and slower.
Keywords: corporate reputation; fake news; crisis communication.